Hybrid forms of privatisation - Rus, Veljko (Družboslovne razprave, 1999)
The intransigence of public and private ownership has been the common characteristic of traditional capitalism and socialism. However, this no longer holds true for post-socialist societies oriented towards the liberalisation of society; neither does it hold true for post-capitalist societies, which are now oriented towards the socialisation of the existing systems. According to the thesis above, hybrid forms of privatisation and ownership should be considered highly relevant to both types of societies. Hybrid forms of privatisation create the possibility of some sort of mezzo-corporativism, which allows for a relatively smooth and co-operative relationship between private and public ownership. However, at the same time it also creates ambiguous relationships between stakeholders. This paper will describe such hybrid forms of privatisation in different fields of social services and attempt to evaluate their policy implications.
Keywords: družbene dejavnosti; privatizacija; public sector; javni sektor; zasebni sektor